Folklore, Cohesion and Meaning in Ojaide’s Agbogidi - Emama, Emmanuel Ogheneakpor (NIU Journal of Humanities, 2020)
In linguistics, cohesion is traditionally conceived as a product of the lexical, grammatical and contextual ties within a text. Textual meaning is therefore the product of interplay between linguistic and nonlinguistic categories. Hierarchically, lexical and grammatical cohesive ties generally exert greater influence on textuality as they usually provide more of the meaning engendering properties of text. However, by examining the cohesive value of lexical and grammatical linkages, as well as the context of culture in Agbogidi, one of the folklore-inspired poems of Tanure Ojaide, this paper argues that: (i) lexical and grammatical cohesive linkages are almost insignificant in deciphering the communicative value of the poem under consideration arising from the apparent meaning discursiveness between the lexical items in the poems; (ii) cohesion in the investigated poem is underpinned primarily on socio-cultural semiotics.  A fuller appreciation of meaning in the text is significantly dependent on the knowledge of the Urhobo cultural influences and belief system that permeate the text. Keywords: Cohesion, Context, Cultural Text, Folklore, Meaning, Polysemy